The Effect of Organizational Culture on Business Performance of Small-Medium Enterprises in Fisheries Among Coastal Communities - Mananeke, Lisbeth; Djati, Sundring Pantja; Ingkadijaya, Rahmat; RB, Linda Desafitri (Technium Social Sciences Journal, 2021)
The aim of this study is to determine the effect of organizational culture moderated by competitive advantages on business performance of SMEs in fishery in coastal communities of North Minahasa Regency, North Sulawesi Province, Indonesia. A quantitative method was used to determine the effect. Data were collected by a survey among 200 business actors of SMEs in fishery in coastal communities of North Minahasa Regency. The authors carried out the data analysis by a multiple linear regression technique. Findings of the study show that organizational culture had no positive relationship with business performance of SMEs in fishery among coastal communities. However, simultaneously organizational culture moderated by competitive advantages had a positive and significant effect on business performance of SMEs in fishery among coastal communities of North Sulawesi Regency.